A review on exergy analysis of biomass based fuels - Saidur, Rahman; Boroumandjazi, G.; Mekhilef, Saad; Mohammed, H.A. (Elsevier, 2012)
Renewable energy sources can be a good substitute of the fossil fuels which are being terminated fast. Nowadays biomass and biofuels are considered because of their environment friendly characteristics and their ability of supplying much more energy. An alternative means to select the most efficient and convenient biomass, is exergy analysis. The present paper has reviewed the existent surveys on the exergy analysis of different kind of biomass included the woody biomass, herbaceous and agricultural biomass, aquatic biomass, contaminated biomass and industrial biomass. The most common thermochemical processes are investigated and the efficiency of the different process and various kinds of biomass are determined.